Effect of bergamot essential oil and its constituent linalool on myogenic and neuronally-mediated contractions of human and rat isolated colon: potential benefits in complementary treatment of intestinal diseases - Straface, Marilisa; Andò, Sebastiano; Morrone, Luigi (Università della Calabria, 2020)
Introduction Bergamot essential oil (BEO) is used in aromatherapy and as an additive to food and drink to promote a citrus flavour. In animal models, BEO can modulate the synaptic functions within the Central Nervous System. However, it is not known if BEO can affect the functions of the gastrointestinal tract, despite being widely used in the food industry. BEO and its components linalool, limonene and linalyl-acetate were therefore examined for their ability to influence neuromuscular contractions of human and rat isolated colon. Material and Methods Human colon was obtained at surgery for bowel cancer following informed consent; mucosa-free strips were cut parallel to the circular muscle. Rat colon (Sprague-Dawley) strips were also cut as circular muscle preparations. In most experiments, each strip was suspended between platinum wire electrodes in tissue baths containing Krebs solution (5% CO2 in O2; 37°C) under tension (1 or 2g of tension for rat and human muscle strips, respectively) for recording of isometric contractions in response to stimulation of cholinergic nerves using electrical field stimulation (EFS) or to the application of exogenous stimulants of smooth muscle contraction (acetylcholine (ACh), 5-hydroxytryptamine (5-HT), substance P (SP) or KCl). Cumulative concentration-response curves were obtained for BEO (10-6 - 10-3 % v/v) and its major components linalool, limonene and linalyl-acetate (10-9 - 10-4 M). The inhibition of the amplitude of the contractions by each agent was expressed in percentage terms as the mean  s.e.m of the numbers of patients or animals. Results In preliminary experiments, BEO and its components reduced contractions of rat colon caused by ACh, 5-HT or SP. Subsequently concentration-dependent inhibition of both KCl-evoked contractions and neuronally-mediated contractions were demonstrated in response to BEO or its components, with greater potency when tested on the latter. The inhibitory effect of BEO on myogenic and neuronally-mediated contractions was associated largely via the actions of linalool (apparent pIC50 5.6 ± 0.4, n= 4 on KCl-evoked contractions; apparent pIC50 6.7 ± 0.2, n = 4 on neuronally-mediated contractions) in human colon. Similar but less potent activity of linalool was obtained in rat colon (apparent pIC50 5.4 ± 0.3, n = 4 on KCl-evoked contractions; apparent pIC50 5.8 ± 0.1 %, n = 4 on neuronally-mediated contractions). Conclusion The results indicated that BEO, largely via the actions of linalool, inhibited both human and rat enteric neurotransmission. Some species differences were found in the ability of these substances to inhibit neuronally-mediated contractions; the rank order in terms of potency (apparent pIC50) in human was: linalool > limonene >> linalyl acetate = BEO, and in rat was: linalyl acetate > limonene = linalool >> BEO. Both BEO and linalool were more potent in human muscle strips, acting at least partly by directly inhibiting muscle contractility. These data provide a potential mechanism for their use as a complementary treatment of gastrointestinal diseases related to increased intestinal motility.
Università della Calabria. Dipartimento di Farmacia e Scienze della Salute e della Nutrizione. Dottorato di ricerca in Medicina traslazionale. Ciclo XXXII
Keywords: Olio essenziale di bergamotto; Spasmolitico; Colon